Literasi Lingkungan Hidup Sehat dan Makanan Bergizi untuk Pencegahan Stunting pada Rw. 05 Kelurahan Bandulan, Sukun, Malang - Made Iska A.W.; Pudji Lestari; Dewi Retnowati; Defia Nurbatin; Yudhi Anggoro; M. Roffiudin (Lembaga Pengembangan Kinerja Dosen, 2025)
Stunting is a health problem caused by a lack of nutritious food intake that the body needs. Stunting occurs from the womb, and is visible when the child develops at the age of two years. Literacy about healthy living environments and nutritious food to prevent stunting is very important for families, parents, caregivers, BKB administrators, and community service instructors themselves. Superior human resources come from the formation of character and way of life at an early age in the family. Optimizing the formation, improvement, understanding and role of parents in a healthy living environment and nutritious food needs to be fulfilled to provide the best stunting prevention that can be done.At this moment, the extension team provides assistance in delivering material on a healthy environment and nutritious food to prevent stunting. The delivery of this material serves to provide knowledge and experience related to stunting prevention. And the benefit is that participants get material, knowledge, knowledge and share experiences and solutions so as to produce participants who understand and understand more about a healthy environment and nutritious food to prevent stunting.This service is carried out for BKB participants in the RW. 05 Bandulan subdistrict, Sukun sub-district, Malang city, with around 40 participants. The aim of implementing this service is to help provide environmental literacy programs for healthy living and nutritious food to prevent stunting and change it. It is hoped that this service will also provide benefits for consideration, adding information and insight related to stunting prevention and the performance of BKB RW 05 Bandulan sub-district.